(untitled) (World Economics and Finance Bulletin, 2024)
This article contends that prosecuting individuals and legal entities for their errors is an insufficient solution to the prevailing issues. Instead of resolving problems, such measures may inadvertently give rise to new errors, tax evasion, and inadequate disclosure of income within the tax base. The remedy lies in adopting a scientific approach to prevention. Emphasizing the urgency of these challenges, our research primarily focuses on implementing effective mechanisms. These mechanisms are designed to minimise the adverse effects of violations on state budget revenue formation, emphasizing the need for systematic management to use these preventive measures.